Involvement of Urokinase-Type Plasminogen Activator Receptor in the Formation of a Profibrotic Microenvironment in the Epicardial Region - K. V. Dergilev; Z. I. Tsokolayeva; I. B. Beloglazova; Yu. D. Vasilets; D. O. Traktuyev; B. N. Kulbitsky; E. V. Parfenova (Общая реаниматология, 2021)
The study of the mechanisms of development and progression of fibrosis is one of the key directions of modern cardiology. Our work suggests that the urokinase receptor (uPAR) is involved in the regulation of mesothelial cell activity and epicardial fibrosis development, which, when interacting with specific ligands and intermediate proteins, can activate intracellular signaling, trigger the cascade of proteolytic reactions, including local plasmin formation and activation of matrix metalloproteinases, providing matrix remodeling.Objective: to perform a comparative study of fibrogenic activity of the epicardium in the hearts of uPAR-/- and wild-type animals and evaluate the effect of cardiac microenvironment factors on the migration activity of epicardial mesothelial cells.Material and methods. We used histological and immunofluorescent staining, microarray analysis of proinflammatory cytokine levels, and a method for assessing the migratory properties of epicardial cells.Results. Results. We found that compared to wild-type animals, uPAR-/- animals show significant thickening of the epicardial area (2.46+0.77 (uPAR-/- mice) and 1.02+0.17 (Wt mice) relative units, P=0.033) accompanied by accumulation of extracellular matrix proteins. Deficiency of uPAR gene leads to formation of proinflammatory microenvironment in the heart (increased levels of proinflammatory factors such as IL-1, IL-13, IL-17, RANTES and MIP1), increased migratory activity of epicardial mesothelial cells, accumulation of TCF21+fibroblast/myofibroblast precursors (29.8+13.7 (uPAR-/- mouse) and 3.03+0.8 (Wt mouse) cells per visual field,P=0.02), as well as development of subepicardial fibrosis.Conclusion. These findings suggest that uPAR is a promising candidate for the developing targeted agents to prevent the development and progression of cardiac fibrosis.